Cross-Selling in Bank-Household Relationships: Mechanisms and Implications for Pricing - Basten, Christoph; Juelsrud, Ragnar (Review of Financial Studies, 2026)
Abstract We show that banks cross-sell future deposits and loans to existing household depositors. A bank is 20-percentage-points more likely to sell a loan to an existing depositor than to an otherwise comparable household. Existing depositors pay a premium when borrowing, and we find no indication that banks obtain an informational advantage on such borrowers, suggesting that the cross-selling is driven more by demand than by supply complementarities. These demand complementarities are in turn driven more by stickiness rather than by unobserved persistent preferences. Finally, banks internalize future cross-selling potential when setting deposit rates. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online